Ownership Structure and Company Value's Impact on Corporate Social Responsibility (CSR) - Listianawati, Listianawati; Hersugondo, Hersugondo (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2023)
The study's key objective is to explore how ownership structure and company values impact CSR implementation in listed Indonesian non-financial enterprises from 2019 to 2022. Research data was obtained from secondary data such as Bloomberg and company annual reports, then studied using the multiple linear regression method using SPSS software. The ownership structures studied include managerial, institutional, and foreign ownership. Meanwhile, company values are proxied by Tobin's Q. Meanwhile, Corporate Social Responsibility (CSR) is measured through ESG scores from Bloomberg. The findings show that management and institutional ownership negatively influence CSR, but the company's value has a considerable beneficial impact. However, foreign ownership does not have an impact on CSR. These findings indicate that CSR practices in Indonesian companies tend to be influenced by ownership structure and company values. These findings have practical consequences for regulators and business executives interested in increasing CSR operations.